2015
DOI: 10.1007/s12026-015-8651-3
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-specific ETS-1 (ESE1/ELF3) regulates apoptosis of intestinal epithelial cells in ulcerative colitis via accelerating NF-κB activation

Abstract: Epithelial-specific ETS-1 (ESE1), also named as ELF3, ERT and ESX, belonging to the ETS family of transcription factors, exerts multiple activities in inflammation, epithelial differentiation and cancer development. Previous data demonstrated that ESE1 synergizes with NF-κB to induce inflammation and drive tumor progress, and the nuclear translocation of ESE1 promotes colon cells apoptosis. However, the expression and biological functions of ESE1 in ulcerative colitis (UC) remain unclear. In this study, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…ERG mediates AD-like neurodegeneration in Down's syndrome 31 ; RXRA alters brain cholesterol metabolism in AD 32 ; and STAT3 mediates amyloid--induced apoptosis, the classical hallmark of AD 33 . We identified ELF3 in CD, which is over-expressed in ulcerative colitis (UC) cases 34 , supporting prior work suggesting CD and UC share common genetic factors 35 . We identified MEF2A in CAD, which has been previously identified in linkage studies of autosomal dominant CAD 36 .…”
Section: Motif Enrichment Of Upstream Regulatorssupporting
confidence: 81%
“…ERG mediates AD-like neurodegeneration in Down's syndrome 31 ; RXRA alters brain cholesterol metabolism in AD 32 ; and STAT3 mediates amyloid--induced apoptosis, the classical hallmark of AD 33 . We identified ELF3 in CD, which is over-expressed in ulcerative colitis (UC) cases 34 , supporting prior work suggesting CD and UC share common genetic factors 35 . We identified MEF2A in CAD, which has been previously identified in linkage studies of autosomal dominant CAD 36 .…”
Section: Motif Enrichment Of Upstream Regulatorssupporting
confidence: 81%
“…This demonstrates that TLR4 knock-down is protective against IR injury in the local intestine and the distal lung organ through the NF-κB pathway. Since NF-κB is reported to be a major route for apoptosis in a variety of cell types including the intestinal epithelial cells [37] and pulmonary microvascular epithelial cells [38], we evaluated the expression of caspase-3, an “effector” protease in the apoptotic cascade, which is usually marked in intestinal IR. Consistent with our expectation, the results in our study showed that caspase-3 expression in the lung tissues was significantly decreased by TLR4 knock-down after IR.…”
Section: Discussionmentioning
confidence: 99%
“…Reports show that ESE1 not only participates in inflammation but also in cell apoptosis. ESE1 regulates apoptosis of intestinal epithelial cells in ulcerative colitis [27] and orchestrates a positive feedback loop that constitutively activates NF-κB and drives prostate cancer progression [39]. Our study showed that ESE1 could increase neuronal apoptosis and NF-κB activity in neurons in response to CM.…”
Section: Ese1 Regulates Apoptosis Of Neurons In Cns Inflammation Via mentioning
confidence: 69%
“…LPS induces the activation of pro-inflammatory cytokines, and other signaling pathways that ultimately lead to apoptosis and cell death. ESE1 also regulates apoptosis of intestinal epithelial cells in ulcerative colitis via accelerating NF-κB activation [27,28]. However, the role of ESE1 in neuron in CNS inflammation model is still unclear.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
See 1 more Smart Citation